2021
DOI: 10.1002/gj.4361
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of surface water and groundwater giving emphasis on water quality index and irrigational indicators in the southeastern part of Manipur Valley, north‐east India

Abstract: Water quality index (WQI) and irrigational indices for surface water and groundwater in the southeastern part of Manipur Valley in north‐east India has been examined. The water samples were collected during the pre‐monsoon season in the year 2016. Geologically, the Manipur Valley occurs as an intermontane piedmont‐alluvial plain filled with Quaternary alluvium of fluvio‐lacustrine origin. The basic chemical parameters of pH, total dissolved solids, electrical conductivity, total hardness, Cl−, HCO3−, Na+, Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Thokchom and Kshetrimayum (2021) elucidated the water quality status of surface water and groundwater using irrigational parameters and WQI for drinking and irrigation purposes in the south‐eastern part of Manipur Valley of North‐east India. The basic chemical parameters of pH, total dissolved solids, electrical conductivity, total hardness, Cl − , HCO 3 − , Na + , Ca 2+ , Mg 2+ , Fe, Mn, Zn, etc., it is suggested that about 20% of the piedmont zone groundwater are unsuitable for both drinking and agricultural purposes.…”
Section: Research Outputs Of Special Issue‐ Partmentioning
confidence: 99%
See 2 more Smart Citations
“…Thokchom and Kshetrimayum (2021) elucidated the water quality status of surface water and groundwater using irrigational parameters and WQI for drinking and irrigation purposes in the south‐eastern part of Manipur Valley of North‐east India. The basic chemical parameters of pH, total dissolved solids, electrical conductivity, total hardness, Cl − , HCO 3 − , Na + , Ca 2+ , Mg 2+ , Fe, Mn, Zn, etc., it is suggested that about 20% of the piedmont zone groundwater are unsuitable for both drinking and agricultural purposes.…”
Section: Research Outputs Of Special Issue‐ Partmentioning
confidence: 99%
“…The Himalaya mountain belt is about 2500 km in length, from west to east, and is a classic example of an orogenic system created by the continent-continent collision between the Indian-Eurasian plates F I G U R E 2 Geological map of Eastern Himalaya, Indo-Myanmar orogenic belt, northern, Central Myanmar, and adjacent areas (modified after Mitchell et al, 2007;Searle et al, 2007;. Locations of study area presented in the issue include 1/S2: Kundu and Hazarika (2022); 2/S2: Y. R. ; 3/S2: Rawat and Luirei (2022) Chaubey et al (2022); 24/S2: ; Bora, Mukherjee, et al (2022); 25/S2: Khuman and Ibotombi (2022); 26/S2: Y. R. ; 27/S2: Thokchom and Kshetrimayum (2021); 28/S2: Barman et al (2022); 29/S2: V. Sharma and Biswas (2022) along the Indus-Tsangpo Suture Zone (ITSZ) $55 Ma ago (de Sigoyer et al, 2000;DeCelles et al, 2001;Yin, 2006). The southern parts of the Eurasian Plate mainly have the Trans-Himalaya, Ladakh batholith, Gangdese batholith, Lohit batholith, Karakoram Ranges, Ophiolites, Indus-Tsangpo Mélange zone, etc.…”
Section: Himalaya Orogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Water quality is generally referred to the biological, chemical, and physical characteristics of water that define its drinking potability and suitability for various applications in fishing, agriculture, and industrial processes [3]. Assessment of the water quality is based on the presence and levels of physicochemical parameters such as pH, total dissolved solids, hardness, conductivity, anions and cations, biological components, and heavy metals [4], [5].…”
Section: Introductionmentioning
confidence: 99%